Os limites do financiamento cultural federal no Brasil: Entre ideias e materialidades - Frederico Augusto Barbosa da Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– This text describes the structure of federal funding of culture, its dynamism and composition. It analyzes the expenses of the Ministry of Culture, its evolution and changes of composition. It also looks at the incentive resources, part of the federal funding system, which are deployed in new corporate resources and in the Union's fiscal waiver. Financing is considered part of the public policy instruments having an ideational dimension, pluralization of sources, direct support for the arts and culture, encouragement of private mentoring through incentives, conservation and strengthening of the State to carry out public policies etc. Financing is considered part of the public policy instruments, having a symbolic dimension where ideas and justifications appear as a pluralization of sources, direct support for the arts and culture, encouragemente of private mentoring through incentives, conservation and strengthening of the State to carry out public policies etc. Associated with these ideas are innumerable controversies, among them the senses of relations State/market, disreponsibilization of the State by cultural public policies, predominance of the interests of big corporations etc. However, the policy instruments can be seen by their results, in the effective and material actions that are mirrored in the structure of the expenditures, in the concrete and selective support to groups and in the distribution of resources in the territory. Thus, the discussions that follow link the idea and materialities present in the financing, following some of the controversies about the instruments and results of the federal funding system of culture
Keywords: Z18; 330; cultural financing system; direct expenses; tax breaks; cultural budget